A study on factor affecting the effectiveness of training provided to staffs of Office of Registrars in Universiti Teknologi Malaysia, Johor Bahru / Nor Amira Syairah Zulkarnaini - Zulkarnaini, Nor Amira Syairah (Faculty of Business and Management, 2013)
This study attempted to identify the factors that affecting the effectiveness of training provided to staffs of Office of Registrars in UTM in order to improve the job performance. The implication for the study is the organization to focus on consistently sustaining the organizational learning culture with the required superior support and the application of skill and knowledge to improve training effectiveness. The purpose of this study is to examine the factors that influencing the training effectiveness in terms of employee of Office of Registrars in Universiti Teknologi Malaysia. Sixty employees from Office of Registrars in UTM were involved in this study. Questionnaires were distributed among the respondents.